Exploring resilience in the affect regulation of family violence-exposed adolescents: « des fois ça marche, des fois, ça [ne] marche pas » - Maurer, Katherine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2020)
Objectives: The study explores the presence of the three components of Ungar’s (2019) biopsychosocial process definition of resilience in the context of family violence-exposed adolescents’ descriptions of affect regulation when experiencing high affect arousal. Methods: A convenience sample of 16 youth, age 15-25 with histories of family psychological, and/or physical violence exposure, completed semi-structured qualitative interviews describing affect regulation during arousal states in past stressful situations. Interviews were recorded and transcribed verbatim. Utilising deductive framework analysis, predefined thematic coding was conducted in NVivo. Results: Rich descriptions were generated of youth’s adaptive capacities to regulate affect while under stress. We explored the presence of the three components of Ungar’s (2019) resilience definition in the data: 1) Risk affect regulation during hyper-/hypo-arousal states, 2) Navigation of access to and negotiation for meaningful promotive and protective internal and external factors, and 3) Resilience outcomes of recovery, adaptation, and transformation. The framework analysis of Ungar’s (2019) resilience definition illuminated differential interactions between adolescents and access to resources in their environments. Despite some resource deficits, participants demonstrated adaptive resilience when regulating affect. Implications: Ungar’s (2019) process resilience definition highlights the interconnection between youth’s resource needs and the capacity of their environments to provide them to enhance resilience. Results suggest that interventions to increase resilience should incorporate the full biopsychosocial ecological process model with a focus on regulation capacity. The knowledge gained from youth perspectives of affect regulation processes is directly applicable to complex trauma-informed interventions to increase self-regulation and resilience while reducing behavioural reactivity for violence-exposed adolescents.